2020
DOI: 10.17263/jlls.712854
|View full text |Cite
|
Sign up to set email alerts
|

Move analysis of research article abstracts in the field of ELT: A comparative study

Abstract: This study aims to make a comparison between research article abstracts written by two groups in the field of English Language Teaching (ELT) by Turkish scholars and non-Turkish scholars working in Anglophone countries to find the rhetorical structure they employ in their abstracts. To achieve this purpose, 390 research article abstracts, 195 abstracts from each group, were analyzed. To analyze the abstracts, Hyland's (2000) model with five moves was employed. In addition to the descriptive statistics, the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…is might imply the authors' cognizance of the crucial role of these three moves in drawing the scholarly readers' attention to the full paper [13]. Moreover, the findings were commensurate with Santos's [17] results which revealed the obligatory nature of these moves in applied linguistics abstracts.…”
Section: Move Occurrencesupporting
confidence: 69%
See 4 more Smart Citations
“…is might imply the authors' cognizance of the crucial role of these three moves in drawing the scholarly readers' attention to the full paper [13]. Moreover, the findings were commensurate with Santos's [17] results which revealed the obligatory nature of these moves in applied linguistics abstracts.…”
Section: Move Occurrencesupporting
confidence: 69%
“…However, the results contrasted their study in that they demonstrated the low frequency of the occurrence of the conclusion move in their corpora. With regard to these two moves, the findings of the current study might signify the authors' tendency to take heed of presenting the topic and the existing void before articulating the purpose of the study [13]. Besides, the authors of the abstracts in both IJEAP and JEAP preferred to reckon with the implications of their research findings.…”
Section: Move Occurrencementioning
confidence: 82%
See 3 more Smart Citations